Energy Consumption and Performance of Sectoral Outputs: Results from an Energy-Impoverished Economy - ISHIORO, Bernhard (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.9.7(31).17, 2019)
This paper is directed at exploring the relationship among energy consumption, disaggregated sectoral output (GDP) and economic growth in Nigeria using time series data. The study applied a plethora of estimation techniques (multivariate unit root, Johansen cointegration and Granger causality tests). The study found that energy consumption has enhanced the performance of agriculture, health, manufacturing, utilities, finance and transport sectors in Nigeria during the period under consideration. Long-run energy consumption was found to be detrimental to the performance of administration output (GDP). The study recommends that energy consumption should be encouraged essentially for sectoral and industrial purposes (the production of intermediate goods and services) and not only for household consumption.